Studies on the use of orange peel oil and ethanol in an unmodified agricultural diesel engine. Issue 15 (3rd August 2019) - Deep, Amar; Kumar, Rakesh; Kumar, Naveen
ABSTRACT: The aim of the present study is to investigate the suitability of Orange peel oil and ethanol blends as an alternative fuel for CI engine. Various blends of ethanol with Orange peel oil were prepared on volumetric basis and named as E5OPO95 (5% ethanol and 95% Orange peel oil), E10OPO90 (10% ethanol and 90% Orange peel oil), E15OPO85 (15% ethanol and 85% Orange peel oil) and E20OPO80 (20% ethanol and 80% Orange peel oil). All blends were found to be homogeneous and various physicochemical properties are evaluated in accordance with relevant standards. In the subsequent phase of this investigation, exhaustive engine trials were carried out on a single cylinder medium capacity diesel engine using the different test fuel samples. The result shows a marginal reduction in the brake thermal efficiency for all blends as compared to diesel. At the same time, NOx decreased slightly for all blends. The HC emissions were found to increase while CO2 emissions decrease for different ethanol Orange peel oil blends as ethanol content increased. Moreover, the smoke opacity and exhaust gas temperature were found lower than neat diesel for all the blends.